Improvement of the noradrenergic symptom cluster following treatment with milnacipran - Kasper S (Dove Medical Press, 2011)
Siegfried Kasper, Diana Meshkat, Alexandra KutzelniggDepartment of Psychiatry and Psychotherapy, Medical University of Vienna, Vienna, AustriaAbstract: Depression has a major impact on social functioning. Decreased concentration, mental and physical slowing, loss of energy, lassitude, tiredness, and reduced self-care are all symptoms related to reduced noradrenergic activity. Depressed mood; loss of interest or pleasure; sleep disturbances; and feelings of worthlessness, pessimism, and anxiety are related to reduced activity of both serotonergic and noradrenergic neurotransmission. The importance of noradrenergic neurotransmission in social functioning is supported by studies with the specific norepinephrine reuptake inhibitor reboxetine. In healthy volunteers, reboxetine increases cooperative social behavior and social drive. A placebo-controlled study in depressed patients comparing reboxetine with the selective serotonin reuptake inhibitor (SSRI) fluoxetine showed significantly greater improvement in social adaptation with reboxetine. Two recent studies have examined the effect of the serotonin and norepinephrine reuptake inhibitor milnacipran on social adaptation. A study in depressed patients found that at the end of 8 weeks of treatment with milnacipran, 42.2% patients were in remission on the Social Adaptation Self-evaluation Scale (SASS). Another study in depressed workers or homemakers found that mean depression scores were significantly reduced after 2 weeks, whereas the SASS scores were significantly improved after 4 weeks. A preliminary study comparing depressed patients treated with milnacipran or the SSRI paroxetine showed that milnacipran treatment resulted in a greater number of patients in social remission. The available data thus suggest that milnacipran may improve social functioning, with a possibly greater effect than the SSRI paroxetine. These preliminary data suggest further evaluation of social dysfunction and its treatment outcome in future trials of milnacipran.Keywords: social functioning, Social Adaptation Self-evaluation Scale (SASS), depression, noradrenergic neurotransmission, serotonin and norepinephrine reuptake inhibitors (SNRIs), milnacipran